Competitive Binding of Methylene Blue to Calf Thymus DNA and Carrageenan: Implications for Sensor Development - Hassan, Riyadh Abdulmalek; Heng, Lee Yook; Hanifah, Sharina Abu; Al-badai, Fawaz (Thamar University Journal of Natural & Applied Sciences, 2024)
Carrageenans are sulfated polysaccharides widely used in the food industry due to their excellent thickening, stabilising, and gelling properties. Objective: This study delves into two key aspects: 1) the binding interaction between the cationic dye methylene blue (MB) and carrageenan compared to other polyanions (alginate, starch, and Arabic gum), and 2) the competitive binding behavior of carrageenan and DNA for MB. Methods: Spectroscopy methods were employed to determine the total amount of carrageenan by utilising MB, which creates complexes with carrageenan. The investigation into the competitive binding between polysaccharides and double-stranded DNA modified with screen-printed electrodes (SPEs) (dsDNA/SPE) for methylene blue (MB) involved the addition of varying quantities of polysaccharide to a solution containing 100 µM MB after a 5-minute accumulation period. Subsequently, cyclic voltammograms were directly recorded to analyse the interactions. Results: Strong electrostatic binding between MB and carrageenan was confirmed using various techniques, including UV-vis, fluorescence, and cyclic voltammetry. Moreover, photoluminescence (PL) spectroscopy was more sensitive than Ultraviolet-visible (UV-vis) spectroscopy,  detecting carrageenans in a linear range from 0.5-15 ppm, 2-15 ppm, with correlation coefficients 0.998, 0.997, respectively. Notably, the preference for binding increased with increasing sulfate content, following the order kappa > iota > lambda carrageenan, highlighting the crucial role of sulfate groups in complex formation. Additionally, carrageenan exhibited the strongest competitive binding towards MB at low concentrations compared to other tested polyanions, implying its effectiveness in hindering MB-DNA interactions. Conclusions: These findings pave the way for exciting developments in DNA biosensors. The sensitive colorimetric assay holds promise for the rapid and selective determination of carrageenan levels in food products. Moreover, the competitive binding between carrageenan and MB can be harnessed in DNA biosensors by monitoring changes in MB binding due to specific DNA sequences.